2018
DOI: 10.1007/s00726-018-2539-1
|View full text |Cite
|
Sign up to set email alerts
|

Selection and identification of novel peptides specifically targeting human cervical cancer

Abstract: Cervical cancer is the second most commonly diagnosed cancer and the third leading cause of cancer deaths among females in underdeveloped countries. This study aimed to identify several novel cervical cancer-specific targeting peptides (CSPs) to provide new methods for the effective diagnosis and treatment of cervical cancer. Peptide library screening in vivo was performed on human cervical cancer xenografts with Ph.D.™-12 and C7C phage display peptide libraries. Two specific peptide sequences (GDALFSVPLEVY an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Considering the misleading results, the authors concluded that care should be taken when using labelled bacteria in phagocytosis assays. FITC was also used for specifically targeting of human cervical cancer cells (Liu et al 2018). For this purpose, cancerspecific targeting peptides (CSPs) were labelled with FITC.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the misleading results, the authors concluded that care should be taken when using labelled bacteria in phagocytosis assays. FITC was also used for specifically targeting of human cervical cancer cells (Liu et al 2018). For this purpose, cancerspecific targeting peptides (CSPs) were labelled with FITC.…”
Section: Introductionmentioning
confidence: 99%
“…Although, in recent decades, some progress has been made in the prevention, diagnosis, and treatment of CC, the overall survival rate is still poor, especially metastatic patients. 7 The 5-year survival rate of localized CC patients is 91.5%, while the 5-year survival rate decreases to 57.1% and 17.3% with patients who suffer from regional lymph node metastases and diatant metastases, respectively 8 . Moreover, the incidence of CC is still high, and 80% patients have developed to invasive cancer at the time of diagnosis.…”
mentioning
confidence: 99%
“…Moreover, the incidence of CC is still high, and 80% patients have developed to invasive cancer at the time of diagnosis. 8 Therefore, it is urgent to further reveal the molecular mechanism of the occurrence and development of CC and find biomarkers for early diagnosis, metastasis and prognosis, and new effective therapeutic targets.…”
mentioning
confidence: 99%
“…28 Cancer chemotherapy based on peptides has historically attracted considerable interest due to the unique advantages of peptides, such as their low molecular weight, ability to specifically target tumor cells, and low toxicity to normal tissues. 29 Since the approval of sipuleucel-T by the US Food and Drug Administration (FDA) as the first standard peptide vaccine for prostate tumors, an increasing number of peptides have been tested in many other types of cancer, such as melanoma, glioblastoma, breast cancer, and gastric cancer. [30][31][32] In breast cancer, strategies for peptide chemotherapy have been proposed as vaccines to improve immune efficacy.…”
Section: Discussionmentioning
confidence: 99%